The Criminal Punishment of LGBTQ: A Comparative Study of Nigerian and Indonesian Laws - Putri, Windy Virdinia; Fuadi, Gumilang; Susila, Muh. Endrio (Universitas Muhammadiyah Malang, 2023)
This study aims to compare the punishment for LGBTQ in Nigeria and Indonesia so the similarities and also the differences between the two legal systems can be drawn. This research is normative research using a comparison method. This study found that: First, there are similarities in the adopted legal systems, namely they both adhere to colonial heritage law, customary law, and Islamic law (Sharia). Regarding Sharia Law, the Sharia penal law adopted in the northern states of Nigeria and through Sharia Regional Regulation in parts of Indonesia, namely Aceh Province based on Special Autonomy, allows the province to form regional regulations based on Islamic Law (Sharia). Furthermore, there are similarities in terms of punishment based on Sharia punishment for Nigeria and Indonesia, namely that they both apply to cane, except for male sexual intercourse is punishable by stoning to death based on Nigeria Sharia punishment. Second, there are differences in the prosecution of LGBTQ people based on applicable national law. In Nigeria, based on the Criminal Act, anyone who has sexual intercourse with the same sex or with an animal or allows a man to have intercourse with another man or with a woman through anal intercourse is convicted of a crime and punished with imprisonment for 14 years. In Indonesia, based on the current Criminal Code, it only prohibits homosexual acts between an adult and a child of the same sex. In other words, the actions of two or more adult men cannot be prosecuted by criminal law, and the perpetrators cannot be punished, including if the